The Implementation Of K-Means Clustering Method To Product Sales Data At Pratama Elektronik Shop, Taba Lagan Village, Central Bengkulu Regency - Yoga Putra Pratama; Jusuf Wahyudi; Eko Suryan (Jurnal Media Computer Science, 2026)
The implementation of K-Means Clustering method to product sales data at Pratama Elektronik shop, Taba Lagan Village, Central Bengkulu Regency, can assist store management in grouping sales data automatically and in a computerized manner, as well as providing information regarding product sales patterns that can be used to support decision-making, particularly in inventory management. The clustering results consisted of three groups: Cluster C1 (high-sales category), Cluster C2 (medium-sales category), and Cluster C3 (low-sales category). Based on testing using 100 sales data records from Pratama Elektronik shop, Taba Lagan Village, the results showed that 76 products were classified in the low-sales category, 21 products were classified in the medium-sales category, and only 5 products were classified in the high-sales category.